2023
DOI: 10.1001/jamanetworkopen.2023.3125
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Child Firearm Assault Injuries by Race and Ethnicity During the COVID-19 Pandemic in 4 Major US Cities

Abstract: This cross-sectional study examines changes in rates and disparities of fatal and nonfatal firearm assaults among children in New York, Los Angeles, Chicago, and Philadelphia before and during the COVID-19 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…By the end of the study period, exposure was roughly comparable across age cohorts but exposure was consistently lowest among White youth. Other recent work, such as a 2023 study by Jay et al, reported that during the pandemic, Black children were 100 times, and Hispanic children 25 times, more likely than White children to be shot in Chicago and other major US cities.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…By the end of the study period, exposure was roughly comparable across age cohorts but exposure was consistently lowest among White youth. Other recent work, such as a 2023 study by Jay et al, reported that during the pandemic, Black children were 100 times, and Hispanic children 25 times, more likely than White children to be shot in Chicago and other major US cities.…”
mentioning
confidence: 96%
“…Young people’s exposure to firearm violence in US cities has surged during the COVID-19 pandemic . This study by Lanfear and colleagues examines how long-term changes in firearm violence have influenced exposure across multiple birth cohorts in Chicago, Illinois.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Firearm injury is associated with increased severity of adverse health outcomes and mental health needs, further compounding existing health and racial inequities among survivors and communities . Adult and pediatric survivors experience high rates of posttraumatic stress disorder, anxiety, and depression .…”
Section: Introductionmentioning
confidence: 99%
“…Inequities in firearm injuries in major US cities increased during the COVID-19 pandemic. Black children were 100 times more likely and Hispanic or Latino children were 25 times more likely to sustain firearm injuries than non-Hispanic White children . Urban communities with concentrated poverty experience disproportionately more firearm homicides, crime, and associated trauma than less disadvantaged neighborhoods .…”
mentioning
confidence: 99%